Optimism, resilience, sense of humor and health of people with a partner - Flórez, Nicole; Sánchez Aragón, Rozzana (Pensando Psicología, 2019)
Introduction: Relationships become the most important link for the human being since they encourage and enrich certain individual attributes that are made evident through romantic interaction. An example of this are the constructs of: optimism, resilience and positive humor - among others – that contribute to the mood, satisfaction with life, well-being and health of people. Objectives: (1) Identify the levels of optimism, resilience, sense of humor and health; (2) Examine the possible differences according to sex in these variables and; (3) Understand the degree of association between optimism, resilience and sense of humor with the health of men and women with partners. Methodology: A correlational and comparative study was carried out with a non-probabilistic sample of 240 people for convenience; adults (50% women and 50% men), aged between 18 and 75 years old, with a minimum schooling of high school and a minimum relationship time of six months. Results: The positive relationship between optimism, resilience and sense of humor with health, especially with the vitality factor, is highlighted; along with negative relationships associated with some factors that indicate health problems. As for the differences by sex, men were found to possess greater self-confidence, strength, social support, creativity / ingenuity, social humorous orientation, prudence, dark humor and vitality compared to women, who only scored high on hope and humorous passivity.